Peran Etika Bisnis dalam Perusahaan Bisnis di Era Globalisasi - Muhammad Andre Alkahfi; Zuhrinal M. Nawawi (VISA: Journal of Vision and Ideas, 2023)
When it comes to establishing relationships with others in the business world, ethics plays an important role. Business ethics plays an important role in determining the success or failure of a company. Practicing good corporate ethics can also improve communication and foster mutual trust between colleagues. In running a company, you have to focus on two things. The first is aware of and considers the needs and emotions of others. The second reason is to avoid avoiding other people, because corporate ethics vary widely between cultures and countries. The purpose of writing this article is to find out how Business Ethics in Business Companies in the Globalization Era. The author of this article uses observation techniques as a research strategy, as well as library research methods. Based on the discussion in this article, the level of trust that each member of the business community has with each other is influenced by business ethics. There are a variety of stakeholders impacting each other, including businesses, suppliers and end users. Each of these components must uphold ethical standards so that the foundation of trust is well maintained. Keywords: Bussiness,Ethics, Globalization, Company